Technical Infrastructures of Historical Translation Knowledge: A Call for the use of the Digital Library and Bibliography of Literature in Translation: or: Invitation to Communism - Schippel, Larisa; Richter, Julia; Rozmyslowicz , Tomasz; Kremmel, Stefanie (chronotopos – A Journal of Translation History, 2022)
Editorial in English and German on the technical infrastructures relevant for translation history. The editors share an invitation to make use of the Digital Library and Bibliography of Literature in Translation (DLBT) and discuss the needs of translation historians and the trends in translation history in regards to principles of open science and communism as described by Robert Merton.